A new enantioselective CE method for determination of oxcarbazepine and licarbazepine after fungal biotransformation. Issue 19 (18th August 2014) - Bocato, Mariana Zuccherato; Bortoleto, Marcela Armelim; Pupo, Mônica Tallarico; de Oliveira, Anderson Rodrigo Moraes; Chankvetadze, Bezhan
<x xml:space="preserve">Abstract</x> The present work describes, for the first time, the simultaneous separation of oxcarbazepine (OXC) and its active metabolite 10‐hydroxy‐10, 11‐dihydrocarbamazepine (licarbazepine, Lic) by chiral CE. The developed method was employed to monitor the enantioselective biotransformation of OXC into its active metabolite by fungi. The electrophoretic separations were performed using 10 mmol/L of a Tris‐phosphate buffer solution (pH 2.5) containing 1% w/v of β‐CD phosphate sodium salt (P‐β‐CD) as running electrolyte, −20 kV of applied voltage and a 15°C capillary temperature. The method was linear over the concentration range of 1000–30 000 ng/mL for OXC and 75–900 ng/mL for each Lic enantiomer (r ≥ 0.9952). Within‐day precision and accuracy evaluated by RSD and relative errors, respectively, were lower than 15% for all analytes. The validated method was used to evaluate the enantioselective biotransformation of OXC, mediated by fungi, into its active metabolite Lic. This study showed that the fungi Glomerella cingulata (VA1) and Beuveria bassiana were able to enantioselectively metabolize the OXC into Lic after 360 h of incubation. Biotransformation by the fungus Beuveria bassiana showed 79% enantiomeric excess for (S)‐(+)‐Lic, while VA1 gave an enantiomeric excess of 100% for (S)‐(+)‐Lic. This study opens a new route to the drug (S)‐(+)‐licarbazepine.